Molecular Dynamics Study of Crack Propagation LAMMPS for Hexagonal Lattice - Shurooq H. Abd alnebee; Hisham M. ali Hasan (Al-Qadisiyah Journal of Pure Science, 2018)
Molecular Dynamics simulation and Large-scale Atomic/Molecular Massively Parallel , Simulator (lammps) of crack propagation for hexagonal lattice, the mechanisms, including emission of dislocation and creation of stacking faults, the time step used (0.044.0.04,0.03, 0.02, 0.01, 0.009, 0.008, 0.007, 0.006, 0.005, 0.004, 0.003, 0.002, 0.001and 0.00001 tau) ,the time step (0.00001 tau( is a good choice in order to avoid large discretization errors, unchanged number of particles, unchanged volume and unchanged energy (NVE) microcanonical ensemble simulations was used, the energy is conservation. In crack code increase (decreases in negative) potential energy because the crack was not initiated, while the crack initiate at step (run) =10600,  while potential energy was (-3.2511epsilon) at step (run) =10600 resulting by breaking the bonds between atoms while the increase in temperature indicates that the crack propagated.